2003
DOI: 10.1038/sj.bjc.6601278
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and childhood cancer: a report from the United Kingdom Childhood Cancer Study

Abstract: The relationship between neonatal vitamin K received by the intramuscular (i.m.) route and the development of leukaemia or other cancers was investigated as part of a national case -control study of childhood cancer, using data abstracted from obstetric and neonatal records. The analyses included 2530 children diagnosed with cancer before 15 years of age, 1174 of whom had leukaemia and 4487 control children without cancer. Overall, 39% of cases and 42% of controls had records of i.m. vitamin K administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…A risk of solid tumours can now almost definitely be ruled out, but a small risk of leukaemia cannot be excluded. [17,35]. When cases of late VKDB started to reappear, Denmark, Canada, Australia and New Zealand responded by reintroducing universal IM prophylaxis, offering oral prophylaxis with repeated doses to those parents refusing the IM injection at birth.…”
Section: Vitamin K Prophylaxis In the Newbornmentioning
confidence: 97%
“…A risk of solid tumours can now almost definitely be ruled out, but a small risk of leukaemia cannot be excluded. [17,35]. When cases of late VKDB started to reappear, Denmark, Canada, Australia and New Zealand responded by reintroducing universal IM prophylaxis, offering oral prophylaxis with repeated doses to those parents refusing the IM injection at birth.…”
Section: Vitamin K Prophylaxis In the Newbornmentioning
confidence: 97%
“…Previous research has shown that most homeopaths do not recommend MMR vaccination. 26,27 However, there has been less publicity over concerns about a possible link between vitamin K and childhood cancer 28 than about MMR. We show in this study that views of immunity associated with homeopathic conceptions of health disease are widespread, while consultation with a homeopath was itself strongly associated with non-compliance.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…The reported association between i.m. injection of vitamin K at birth and childhood cancer (14) has now largely been refuted (15); however, the suprapharmacological vitamin K levels that follow excessive prophylaxis may conceivably have adverse consequences, as yet unrecognized.…”
mentioning
confidence: 99%